2023
DOI: 10.1002/smi.3337
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing pathways from bullying victimization to nonsuicidal self‐injury and to cyberaggression: Do perceived ostracism and depression mediate their links?

Chao Song,
Luming Liu,
Wenchao Wang

Abstract: Bullying victimization is related to increased aggressive behaviour, but little research considers both self‐ (e.g., nonsuicidal self‐injury; NSSI) and other‐directed (e.g., cyberaggression) outcomes. Moreover, little is known about the mediating mechanisms that underlie this relationship. Based on the General Aggression Model, the current study investigates the mediating roles of Perceived ostracism (PO) and depression in the relationship between bullying victimization and cyberaggression/NSSI among emerging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“… 10 Many studies and meta-analyses have confirmed the positive correlation between bullying victimization and cyber aggression among college students. 9 , 11 , 12 Considering that our study group is college students who use the Internet more conveniently, it is necessary for us to pay more attention to college students’ cyber aggression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 Many studies and meta-analyses have confirmed the positive correlation between bullying victimization and cyber aggression among college students. 9 , 11 , 12 Considering that our study group is college students who use the Internet more conveniently, it is necessary for us to pay more attention to college students’ cyber aggression.…”
Section: Introductionmentioning
confidence: 99%
“…14 It can also be assumed that bullying victimization reduces prosocial behavior among college students because aggression and prosocial behavior have a negative link. 15 According to the theory of stress and coping, 7 individuals who have experienced bullying are more likely to feel rejected, 12 which makes them less likely to be pro-social and reluctant to assist others. Also, victims of bullying are often of low social status and have poor peer relationships, 16 which is also detrimental to the development of their prosocial behavior.…”
Section: Introductionmentioning
confidence: 99%